A Simple Macroprudential Liquidity Buffer - Hardy, Daniel (IMF Working Papers; Working Paper ;, 2014)
A mechanism is proposed that aims to reduce the risk of a banking sector liquidity crisis-which is a quintessentially systemic event and thus the object of macroprudential policy-and moderate the effects of a crisis should one occur. The instrument would give banks more incentive to build up buffers of systemically liquid assets as a proportion of their total liabilities, yet these buffers would be usable in times of stress. The modalities of the instrument are considered with a view to making it effective, efficient, and robust.